MENGENALKAN KOSAKATA BAHASA INGGRIS MELALUI PENGADAAN LES BAHASA INGGRIS GRATIS BAGI SISWA SEKOLAH DASAR (SD) DI NAGARI TLUK AMPLU INDERAPURA - Erniyati, Yelni; Safitri, Santi (Institut Agama Islam Negeri Kerinci, 2021)
English is a language that has been used in most countries in the world, in Indonesia itself English acts as a foreign language which has been studied since elementary school (SD), but unfortunately not all elementary school students get the same opportunity to learn it, infrastructure and the lack of teaching staff is one of the factors that causes this to happen. Based on the facts encountered by the author in Tluk Amplu Inderapura village, elementary school (SD) students from grade 1 to grade 6 have never studied English specifically at their school, this is very inversely proportional to elementary schools in general who have started and introduce simple vocabulary to their students as an introduction to English. Therefore, the writer feels the need to introduce English to elementary school students in this village by holding free tutoring. The purpose of this activity is to introduce English vocabulary to elementary school students in Tluk Amplu Inderapura village in a fun and enjoyable way and free of charge. The author uses songs as a method to introduce alphabets, numbers and various simple vocabulary to make it easier for students to understand and make the learning process more enjoyable. The results of this study indicate that students' interest in English has increased, as evidenced by the large number of students who come to study. In general it can be said that this research went quite well and found good results, the students there began to master a few English words and had an interest in learning English independently without any coercion from other parties.